2017
DOI: 10.21315/aamjaf2017.13.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Risk Anomaly: Evidence from The Thai Stock Market

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
0
0
3
Order By: Relevance
“…Zaremba (2016) also studied the parallels between the country-level and the stock-level low-risk anomalies and found that country-level returns were positively related to standard deviation, value at risk, and idiosyncratic volatility. Saengchote (2017) confirmed that the abnormal returns associated with investment in low-beta stocks were significant and robust in Thai stock market. Fan and Du (2017) empirically examined the mean spillover and the volatility spillover between the CSI 500 stock index futures market and the underlying spot market.…”
Section: Introductionsupporting
confidence: 56%
“…Zaremba (2016) also studied the parallels between the country-level and the stock-level low-risk anomalies and found that country-level returns were positively related to standard deviation, value at risk, and idiosyncratic volatility. Saengchote (2017) confirmed that the abnormal returns associated with investment in low-beta stocks were significant and robust in Thai stock market. Fan and Du (2017) empirically examined the mean spillover and the volatility spillover between the CSI 500 stock index futures market and the underlying spot market.…”
Section: Introductionsupporting
confidence: 56%
“…Studi mengenai asset pricing perlahan mulai bermunculan di kawasan ASEAN seperti penelitian yang dicetuskan oleh Namira dan Nugroho (2016), Gunathilaka et al(2017) dan Saengchote (2017), mereka memulai dengan penelusuran efek pasar (market effect), efek ukuran (size effect), efek nilai (value effect) dan efek momentum (momentum effect) di negara domisili masing-masing.…”
Section: Pendahuluanunclassified
“…Penelitian-penelitian terdahulu yang sesuai dan mendukung ialah Apergis, Artikis dan Sorros (2011); Fama dan French (2012); Cakici, Fabozzi dan Tan (2013); Hanauer dan Linhart (2015); Balakrishnan (2016); Gunathilaka et al(2017); Saengchote (2017) Berdasarkan hasil pengujian hipotesis dengan CAPM pada Tabel 5.4 didapati persamaan regresi Thailand, Malaysia dan Indonesia mempunyai nilai 0.41, 1.58 dan 2.59 untuk konstanta (intercept) yang artinya jika market excess return (RM-RF), size (SMB), value (HML) dan momentum (WML) nilainya adalah sangat rendah, maka excess return portofolio yang diperoleh sebesar -0.41%, 1.58 % dan 2.59%.…”
Section: 35interpretasi Pengaruh Momentum (Wml)unclassified
See 1 more Smart Citation